DIFFERENTIAL EFFECTS OF ANNONA SQUAMOSA SEED EXTRACTS: ANTIOXIDANT, ANTIBACTERIAL, CYTOTOXIC AND APOPTOTIC STUDY - BIBA, V. S; JEBA MALAR, P.W; REMANI, P (International Journal of Pharma and Bio Sciences, 2013)
The aim of this study was to investigate antioxidant, antibacterial, cytotoxic and apoptotic activities of Annona squamosa L seed petroleum ether extract (ASPE). Antioxidant activity was assessed by DPPH scavenging activity, antibacterial activity was tested using broth dilution technique and antiproliferative activity was evaluated by MTT assay. The apoptosis inducing capacity was detected by Acridine Orange –Ethidium Bromide Staining, Hoechst Staining and Annexin V expression was assessed by flowcytometry. The extract showed antimicrobial activity and free radical scavenging activity, RSA 50 of ASPE was 70.5 µg/ml. The active fraction showed IC50 value 33.8 µg/ml of KB cells. Acridine Orange Ethidium Bromide and Hoechst staining exhibited apoptotic features and Flowcytometry revealed increased levels of Annexin-V expression after treatment with the extract. These results suggest that the active fraction isolated from Annona squamosa seed extracts have strong antibacterial, antioxidant and antitumor activities.